2020
DOI: 10.3233/hsm-190531
|View full text |Cite
|
Sign up to set email alerts
|

Paternalistic leadership and pro-social rule breaking: The moderating roles of psychological empowerment and leader-member exchange

Abstract: BACKGROUND: Pro-social rule breaking (PSRB) is considered a positive deviant workplace behavior. In the Chinese context, paternalistic leadership (PL), combined with benevolent, moral, and authoritarian behaviors, appears to affect subordinates' internal psychology and external behaviors (e.g., PSRB). OBJECTIVE: The purpose of this study was to examine the relationship between PL and PSRB in the Chinese context. It was also hypothesized that psychological empowerment (PE) and leader-member exchange (LMX) moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…For example, Zhang et al (2021) found that temporal leadership, i.e., specific time management practice of employees' time usage during work, positively relates to PSRB which results in innovative job performance. Tu and Luo (2020) found that authoritarian leadership encourages PSRB and moral leadership discourages PSRB. Moreover, Zhu et al (2018) examined that when ethical leaders find employees engaging in deviant behaviors, they consider the motivation behind the action.…”
Section: Antecedents Of Psrbmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zhang et al (2021) found that temporal leadership, i.e., specific time management practice of employees' time usage during work, positively relates to PSRB which results in innovative job performance. Tu and Luo (2020) found that authoritarian leadership encourages PSRB and moral leadership discourages PSRB. Moreover, Zhu et al (2018) examined that when ethical leaders find employees engaging in deviant behaviors, they consider the motivation behind the action.…”
Section: Antecedents Of Psrbmentioning
confidence: 99%
“…Several studies have examined the role of individual factors as moderators. For instance, a survey conducted in China found that psychological empowerment attenuated the association between moral leadership and PSRB (Tu and Luo, 2020). In the same study, psychological empowerment and LMX accentuated the association between authoritarian leadership and PSRB (Tu and Luo, 2020).…”
Section: Review Of the Extant Literature On Prosocial Rule-breakingmentioning
confidence: 99%
“…It appears to influence subordinates' internal psychology and external behaviors, such as PSRB. 26 Pro-social behavior encourages employees to violate the organization's policies to achieve organizational efficiency. To illustrate this perspective, one study explains that inclusive leadership magnifies the effectiveness of employees' behavior, thereby encouraging PSRB practices.…”
Section: Inclusive Leadership and Pro-social Rule Breakingmentioning
confidence: 99%
“…This support allows them to break the rules for the organization's betterment as they know that their leader will understand and appreciate their true intentions. The existing studies have also shown that positive leadership behaviour gives employees the courage to engage in constructive deviance (Tu & Luo, 2020 ). For instance, one study showed that inclusive leadership promotes pro‐social rule‐breaking among employees (Wang & Shi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%